The Influence of Product Design and Green Marketing on BYD Car Purchase Decisions - Tri Lestira Putri Warganegara; Ketut Nermade (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: This study analyzes the influence of product design and green marketing on BYD car purchase decisions. Methodology: This study uses a quantitative approach with primary data collected through questionnaires. The population consists of BYD car customers in Indonesia during the 2024–2025 period, totaling 24,629 individuals. The sampling method employed was non-probability sampling with a purposive sampling approach, selecting respondents based on criteria relevant to the research objectives. Using the Slovin formula with a 10% error rate, 100 respondents were obtained. Data analysis was conducted using multiple linear regression. Results: The results show that product design and green marketing have a positive and significant influence on purchasing decisions, both partially and simultaneously. These findings highlight the importance of developing aesthetically and functionally superior products as well as implementing environmentally friendly marketing strategies to shape consumer preferences and decisions. Conclusions: This study concludes that product design and green marketing significantly influence BYD car purchasing decisions both individually and jointly. Consumers’ positive perceptions of modern design and the company’s commitment to environmental issues serve as key drivers of purchase decisions. Limitations: Although this study shows that product design and green marketing significantly influence BYD car purchase decisions, it focuses only on these two variables and does not consider other factors, such as price, product quality, or brand image. Contributions: This study demonstrates that product design and green marketing significantly influence BYD car purchase decisions, both partially and simultaneously, highlighting the importance of innovative aesthetics and sustainability values in attracting modern consumers.